Synthesis and Characterization of Paraffin/Metal Organic Gel Derived Porous Carbon/Boron Nitride Composite Phase Change Materials for Thermal Energy Storage. Issue 48 (11th December 2018) - Atinafu, Dimberu G.; Dong, Wenjun; Wang, Jingjing; Huang, Xiubing; Wang, Jiawei; Gao, Hongyi; Wang, Ge
Abstract : New shape‐stabilized paraffin/porous carbon materials derived from metal organic gel (cMOG)/boron nitride (BN) composites were prepared by the impregnation method. In the composites, paraffin was used as phase change material, while cMOG as a supporting and loading large paraffin content in the pores owing to high specific surface area and BN employed to enhance the thermal conductivity. The scanning electron microscopy images showed better filler–filler connectivity in BN/cMOG than the individual supporting materials. With the synergy of BN and cMOG, the thermal conductivity of BN/cMOG/PCM composites exhibited up to 232.1 % of pristine PCM and 82.3 % of binary BN/PCM composites at the same wt.‐% of BN. The latent heat as‐synthesized composite attains up to 163.1 J/g with up to 80 wt.‐% of paraffin retained in the composites without any leakage. In addition, the composites revealed enhanced heat transfer performance in both the solid and liquid states. Similarly, the XRD and FTIR analysis showed excellent chemical compatibility between paraffin and the supporting materials. In addition, the composite has high thermal stability, reduced supercooling extent, and better reliability after 200 times thermal cycling, which indicate a promising method for large‐scale thermal energy storage. Abstract : Shape‐stabilized porous carbon materials derived from metal organic gel/BN/paraffin were prepared. They have enhanced heat transfer performance in both the solid and liquid phases and large energy storage capacity.